2021
DOI: 10.1021/acsnano.1c01248
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Self-Cascade Pyrite Nanozymes for Apoptosis–Ferroptosis Synergistic Tumor Therapy

Abstract: As next-generation artificial enzymes, nanozymes have shown great promise for tumor catalytic therapy. In particular, their peroxidase-like activity has been employed to catalyze hydrogen peroxide (H 2 O 2 ) to produce highly toxic hydroxyl radicals ( • OH) to kill tumor cells. However, limited by the low affinity between nanozymes with H 2 O 2 and the low level of H 2 O 2 in the tumor microenvironment, peroxidase nanozymes usually produced insufficient • OH to kill tumor cells for therapeutic purposes. Herein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
234
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 334 publications
(264 citation statements)
references
References 73 publications
9
234
0
Order By: Relevance
“…The correlation of fluorescence with phosphatase activity in anciently processed RP and 230 °C processed RP suggesting the characteristics of the nanoparticles correlate with the nanozyme/herbzyme activity of phosphatase. Compared to the metal-based nanozyme, this natural processed herbal nanozyme seems cost-effective and easily absorbs with potential in drug delivery (Meng et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The correlation of fluorescence with phosphatase activity in anciently processed RP and 230 °C processed RP suggesting the characteristics of the nanoparticles correlate with the nanozyme/herbzyme activity of phosphatase. Compared to the metal-based nanozyme, this natural processed herbal nanozyme seems cost-effective and easily absorbs with potential in drug delivery (Meng et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nanoceria and iron oxide magnetic nanoparticles (Fe 3 O 4 MNPs) are the most widely utilized metal oxide catalysts among the metal oxide-based nanomaterials ( 5 , 8 10 , 16 , 34 , 35 ). Nanoceria exists in a mixed valence state (Ce 3+ and Ce 4+ ) ( 9 , 36 38 ).…”
Section: Classification Of Nanozymesmentioning
confidence: 99%
“…Since the discovery of iron nanoparticles with intrinsic enzyme activity, more than 540 novel nanozymes have been reported with modifications since the first generation of nanozyme type of peroxidase by classical Fe 3 O 4 [3]. Recently Meng et al, for instance, reported an improved peroxidase of pyrite peroxidase nanozyme with super strong binding to substrate hydrogen peroxide (H 2 O 2 ) compared to traditional nanozyme Fe 3 O 4 and protein based horseradish peroxidase, with which additional glutathione oxidase-like activity, following with the catalysis of H 2 O 2 generation [4]. The dual nanozyme finally targeted KRAS mutation with tumor catalytic therapy [4].…”
Section: Introductionmentioning
confidence: 99%